Genetic and non genetic variability in selective value of Hariana cows - KUMAR, ARUN; SINGH, UMESH; KHANNA, A S; SINGH, R P (The Indian Journal of Animal Sciences, 2011)
Data from the calving records of 660 Hariana cows were utilized to study the overall descriptive statistics for total calves born and survived up to first calving in the milking herd from each cow. Average number of total calves produced, total alive calves, total female calves and total female calves reached at milking age per cow during its life time in the herd were 5.2±0.16, 4.9±1.5, 2.38±0.15 and 1.2±0.21. Cow longevity for this herd was 9.12 years, whereas productive herd life was 5.38 years. Average coefficient of gene replication (CGR) was 0.6 ±0.11 for this herd and indicated that this value is higher than one time gene replication (0.5). There was an increasing trend for the total calves born with the increase in the first lactation milk yield (FLMY), higher milk producing cows produced more number of calves as compared to low milk producers. This varied from 2.1±0.28 calves produced by low milk producers (<550 kg) to 6.8±0.36 calves by high milk producers (>1550 kg FLMY). The percentage of cows which left the herd after giving only 1 calf was 21.2, and 11.3% cows produced 10 or more calves in the herd. Effect of age at first calving was not significant on these traits except total alive calves born. Period of birth and FLMY had highly significant effect on these traits. Per cent distribution of cows indicated that 19.3% cows in the herd could not produce any female calf, 25.3% cows left the herd after producing only 1 female calf. About 50% cows left the herd without giving any replacement heifer, whereas 21.4, 12.9 and 8.7% of cows left only 1, 2 and 3 replacements, respectively.